Second ectopic recurrence of mitral valve myxomas after resection - Yuan, Zhize; Li, Haiqing; Chen, Anqing; Zhao, Qiang (Journal of Thoracic Disease, 2018)
Cardiac myxomas are the commonest primary cardiac tumors, accounting for 50% of cases (1). Arising from the endocardial tissue, most of myxomas are located in the left atrium, with the percentage from 75% to 83% of the total; while the percentage in the right atrium is less, up to 10–18%, and they often appear more frequently in the area near to fossa ovalis (1,2).